2019
DOI: 10.1177/0011000019895276
|View full text |Cite
|
Sign up to set email alerts
|

Telepsychology: A Primer for Counseling Psychologists

Abstract: Telepsychology is having a profound influence on professional practice. Currently, however, many psychologists lack the requisite knowledge and skill to provide ethical and competent telepractice services. Moreover, the field has lagged in developing the educational and supervised experiences required to achieve competency. Yet, there is great opportunity as well. The purpose of this article is to identify the natural integration of the pillars of counseling psychology with the major domains of telepractice an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 41 publications
0
34
0
7
Order By: Relevance
“…A survey by American Well in 2015 reached 2,000 participants; two out of three respondents said they would be interested in telehealth services (Cooper et al, 2019). Two meta-analyses have shown that online psychotherapy offers interesting results in the treatment of anxiety and depressive disorders (Barak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A survey by American Well in 2015 reached 2,000 participants; two out of three respondents said they would be interested in telehealth services (Cooper et al, 2019). Two meta-analyses have shown that online psychotherapy offers interesting results in the treatment of anxiety and depressive disorders (Barak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Competency in telepsychology is critical, and providing services in a crisis such as COVID-19 is another critical situation which need further level of training and competency. Competent psychologists, for example, in providing face-to-face interventions, may find that their effectiveness does not transfer to telepsychology services without further training [23] .…”
Section: Resultsmentioning
confidence: 99%
“…Psychologists must be sure that the codes of ethical and professional standards of practice are met during the telepsychology services they provide [14] . Telepsychology does not entail new guidelines but needs awareness of further issues and actions that arise in the context of providing medical care remotely [23] . Three-quarters of the telepsychology guidelines (APA, 2013) are standards of the Ethical Principles of Psychologists and the Code of Conduct [27] .…”
Section: Resultsmentioning
confidence: 99%
“…The Kooth service might therefore be viewed as a positive virtual ecosystem (+VE; Figure 2). Psychological support services are relatively underdeveloped in terms of keeping up with technological advances [60]. Given this, it is common for services to attempt to replicate face-to-face ways of working when developing web-based therapeutic resources and to judge them using the same criteria [61].…”
Section: The Mode Of Delivery: a Positive Virtual Ecosystemmentioning
confidence: 99%